2021
DOI: 10.1371/journal.pone.0253953
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Yellow fever, Chikungunya, and Zika virus at a community level in the Gambella Region, South West Ethiopia

Abstract: Yellow fever (YF), Chikungunya (CHIK), and Zika(ZIK) are among re-emerging arboviral diseases of major public health concern. Despite the proximity of the Gambella Region to South Sudan where arboviral cases have been recorded repeatedly the current epidemiological situation is unclear in this part of southwest Ethiopia. Therefore, we conducted a community-based seroprevalence survey of YF virus (YFV), CHIK virus (CHIKV), and ZIK virus (ZIKV) infections in two selected districts. A cross-sectional study was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Differential risks of CHIKV prevalence for men and women were observed across the world. There are situations where women are more frequently infected than men [12][13][14][15] others where men are more frequently infected than women 16 , and situations were infection rates are similar in both genders 17 . The main explanation for differences lies in the conjunction of occupational and entomological factors.…”
Section: Discussionmentioning
confidence: 99%
“…Differential risks of CHIKV prevalence for men and women were observed across the world. There are situations where women are more frequently infected than men [12][13][14][15] others where men are more frequently infected than women 16 , and situations were infection rates are similar in both genders 17 . The main explanation for differences lies in the conjunction of occupational and entomological factors.…”
Section: Discussionmentioning
confidence: 99%
“…Malnourished individuals and those with weakened immune systems are particularly vulnerable to these types of diseases. Other studies report similar and contrasting findings [ 1 , 2 , 12 , 13 , 17 , 18 , 19 , 20 , 21 ]. These results could also have been influenced by the sampling period.…”
Section: Discussionmentioning
confidence: 61%
“…Seroprevalence rates of 0.7% and 27.3% of arboviral infections have been recorded in Kenya and Ethiopia, respectively [ 19 , 20 ]. There is no known definitive signature work on the cocirculation of malaria, ZIKV, and FLAVI cocirculation antibodies in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…We found no association between an environmental targeted sampling strategy and seroprevalence, however it must be noted that there were limited studies that utilised environmental stratifications of seroprevalence data. Several studies have shown relationships between arbovirus seroprevalence and environmental factors [ 65 , 66 ] and therefore further studies for RRV, BFV and DENV in the PICT would help to further elucidate any environmental trends.…”
Section: Discussionmentioning
confidence: 99%